2017
DOI: 10.1128/jcm.01640-16
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Molds by Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: Although to a lesser extent than diagnostic bacteriology, matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has recently revolutionized the diagnostic mycology workflow. With regard to filamentous fungi (or molds), the precise recognition of pathogenic species is important for rapid diagnosis and appropriate treatment, especially for invasive diseases. This review summarizes the current experience with MALDI-TOF MS-based identification of common and uncommon mold speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
80
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 34 publications
0
80
0
3
Order By: Relevance
“…MALDI‐TOF MS is used in the analysis of portions of mycelium and/or conidia from fungal cultures, and is considered to be an accurate and rapid identification method . The aim of the present study was to evaluate the application of MALDI‐TOF‐MS for the identification of and discrimination between A flavus and A oryzae in clinical and environmental samples and compare its diagnostic power with that of β‐tubulin gene sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…MALDI‐TOF MS is used in the analysis of portions of mycelium and/or conidia from fungal cultures, and is considered to be an accurate and rapid identification method . The aim of the present study was to evaluate the application of MALDI‐TOF‐MS for the identification of and discrimination between A flavus and A oryzae in clinical and environmental samples and compare its diagnostic power with that of β‐tubulin gene sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…For many years, the gold standard for diagnosis of superficial fungal infections has been direct microscopy often performed by the clinician, and culture sometimes supplemented by histopathology. Since the first dermatophyte polymerase chain reaction (PCR) was developed in 1996 an array of new molecular based methods for fungal identification have been developed with different PCR techniques and lately, matrix assisted laser desorption/ionization – time of flight (MALDI‐TOF) mass spectrometry has also been used . Because special equipment is required to perform molecular diagnostics the analysis is performed at specialized mycological or microbiological laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of previous reports have highlighted the importance of supplementing the commercial databases supplied with the various MALDI-TOF platforms with appropriate reference MALDI-TOF spectra in order to improve identification success (29)(30)(31)(32). Since none of the 10 known species included in the test panel employed here were represented in the latest Bruker MSP database, appropriate reference spectra were generated and added to the commercial database.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we recently demonstrated that MALDI-TOF MS could reliably discriminate between a wide variety of clinical and environmental Exophiala species (32). However, in all cases identification accuracy is limited by the availability of appropriate reference MALDI-TOF spectra in the commercial databases supplied with the various MALDI-TOF platforms (29)(30)(31)(32). Here we evaluated whether MALDI-TOF MS could be used to differentiate a variety of filamentous fungi implicated in black-grain eumycetoma and related subcutaneous clinical syndromes.…”
mentioning
confidence: 99%
See 1 more Smart Citation